2019
DOI: 10.1111/ppa.13051
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria from four phylogroups of the Pseudomonas syringae complex can cause bacterial canker of apricot

Abstract: Pseudomonas syringae is described as a species complex, containing P. syringae‐related species classified into 13 phylogroups and 23 clades. Pseudomonas syringae is one of the main pathogens of fruit trees, affecting nut trees, hazelnut and kiwi, pome and stone fruits. Bacterial canker of apricots is an important disease in regions of production with cold winters and conducive soils. This work characterizes the bacteria able to induce canker in apricots isolated in different French orchards. Bacteria from four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Ruinelli et al ( 2019 ) found that a large number of various P. syringae strains are pathogenic on the tested hosts (cherry, peach and almond). Similarly Parisi et al ( 2019 ), isolated four phylogroups (PG01, 02, 03 and 07) able to induce canker on apricot. Ruinelli et al ( 2019 ) suggest the diversity of strains pathogenic on Prunus is probably due to independent evolution of individual strains, not necessarily related to virulence.…”
Section: Discussionmentioning
confidence: 75%
“…Ruinelli et al ( 2019 ) found that a large number of various P. syringae strains are pathogenic on the tested hosts (cherry, peach and almond). Similarly Parisi et al ( 2019 ), isolated four phylogroups (PG01, 02, 03 and 07) able to induce canker on apricot. Ruinelli et al ( 2019 ) suggest the diversity of strains pathogenic on Prunus is probably due to independent evolution of individual strains, not necessarily related to virulence.…”
Section: Discussionmentioning
confidence: 75%
“…This species has been isolated from a variety of environmental sources, including asymptomatic wild plants, snow, epilithic biofilms, and icepacks. either with a single gene or in multilocus sequence analysis (MLSA) using P. viridiflava isolates (Berge et al, 2014;Goss et al, 2005;Parisi et al, 2019;Parkinson et al, 2011;Sarris et al, 2012). It has been suggested that the cts, gapA, or rpoD housekeeping genes alone are sufficient to place a P. viridiflava isolate into its phylogroup in the P. syringae complex (Berge et al, 2014;Parkinson et al, 2011).…”
Section: Taxonomymentioning
confidence: 99%
“…Nine strains of Pseudomonas syringae, the causal agent of bacterial canker of apricot, were inoculated on dormant tissues of twenty apricot cultivars chosen according to their differential susceptibility in orchard conditions. The strains were chosen mainly within phylogroups 1 and 2, the most abundant groups of P. syringae in contaminated apricot orchards in France (Parisi et al 2019).…”
Section: Matrices To 4: Pseudomonas Syringae-prunus Armeniaca (Apricot)mentioning
confidence: 99%